View of southern group of deepsthambhs and dharamshalas - Banganga by Ghosh, Ayan (2023)
The southern end of Banganga Tank had many dharamshalas (rest houses) for pilgrims who stayed for long periods. These were not open to the general public but affiliated with certain castes, professions, or geographic regions. Over time, the Dharamshala has been modified and converted to residential spaces by the current occupants.